Prototipo de herramienta software orientado a dispositivos móviles para apoyar la práctica médica en el área de la ortodoncia - Higuera Ramírez, Saida Rocío; Ramírez Sanguino, Mary Elizabeth; Arguello Fuentes, Henry (Ingeniería, 2011)
This paper describes the analysis, design and development of a software tool intended to be used by orthodontists. The software tool allows collecting, processing and displaying the patient’s data as well as his/her medical history, which provides the specialist with easy-to-use data collection that helps to control his patients’ treatments. We present the results of the project development, which include the design and implementation of two software prototypes: the first one intended for desktop computers and the other oriented to mobile electronic devices. The two software prototypes developed can communicate with each other through a wireless link or via USB ports/sockets. These functionalities ease the process of sharing patients’ information and therefore aid in improving health assistance at the consulting room.